51 Small cell/lymphohistiocytic morphology is associated with CD8 positivity, retained T cell markers, a trend of decreased PD-L1 expression, but not outcome in adults with ALK+ ALCL. (9th November 2020) - Khanlari, Mahsa; Li, Shaoying; Miranda, Roberto N; Iyer, Swaminathan; Yin, Cameron; Lin, Pei; Tang, Guilin; Konoplev, Sergej N; Jeffrey Medeiros, L; Xu, Jie
Abstract : Background: Several morphologic patterns of ALK+ anaplastic large cell lymphoma (ALCL) are recognized: common, small cell, lymphohistiocytic, Hodgkin-like, and composite patterns. 1 Small cell (SC) and lymphohistiocytic (LH) patterns are thought to be closely associated with poorer outcome in children with ALK+ ALCL. 2 However, the clinicopathologic and prognostic features of SC/LH patterns of ALK+ ALCL are not yet reported in adults. Recently, we found PD-L1 expression in a large subset of ALK+ ALCL cases, however, PD-L1 expression in SC/LH versus non-SC/LH ALCL has not been reported. Methods: Among 102 adult patients with ALK+ ALCL seen at our institution from January 1, 2007 through August 30, 2018, 18 (18%) cases had a SC and/or LH pattern. The clinical, pathologic, and outcome data were compared between SC/LH and non-SC/LH ALK+ ALCL cases using Fisher's exact test. Overall survival (OS) was analyzed using the Kaplan-Meier method and compared using the log-rank test. Results: There were no significant differences in clinical features including age, gender, nodal versus extranodal involvement, B symptoms, stage, leukocytosis/lymphocytosis, and serum LDH levels between patients with SC/LH versus non-SC/LH ALK+ ALCL. Compared to non-SC/LH cases, SC/LH ALCL was more often positive for CD2 (92% vs. 36%, p = 0.0007), CD3 (81% vs. 15%, p = 0.0001), CD7 (80% vs. 37%, p = 0.03), and CD8 (54% vs. 7%, p = 0.0006). SC/LH ALCL showed a trend of decreased PD-L1 expression than non-SC/LH cases (24% vs. 46%, p = 0.11). There were no significant differences in the expression of CD4, CD5, CD25, CD43, CD45, CD56, TCR A/B, TCR G/D, cytotoxic markers, EMA, Ki-67 proliferation index. The induction chemotherapy and response rate in patients with SC/LH ALK+ ALCL were similar to patients with non-SC/LH ALK+ ALCL. After a median follow-up of 30.5 months (range, 0.3–224 months), there was no significant difference in OS between patients with SC/LH versus non-SC/LH ALK+ ALCL (p = 0.88). Conclusions: In adults with ALK+ALCL, the SC/LH morphologic pattern is associated with a CD8+ T cell immunophenotype and retention of expression of T cell markers (CD2, CD3, and CD7). The trend of decreased PD-L1 expression in SC/LH ALCL suggests that these patients may not be ideal candidates for PD-L1 immunotherapy. The SC/LH patterns of ALK+ ALCL have no impact on the prognosis of adult patients which is in contrast to the reported association of the SC/LH patterns with poorer outcome in children with ALK+ ALCL. Ethics Approval: The study was approved by the Institutional Review Board at MD Anderson Cancer Center, Approval number: PA16-0897 References: Swerdlow SH, Campo E, The 2016 revision of the World Health Organization classification of lymphoid neoplasms. Blood 2016;127:2375–2390. Brugières L, Deley MC, CD30 (+) anaplastic large-cell lymphoma in children: Analysis of 82 patients enrolled in two consecutive studies of the French Society of Pediatric Oncology. Blood 1998;92:3591–3598.